INTERTEKSTUALITAS PANDANGAN FEMINISME TIRTO ADHI SOERJO DAN MINKE DALAM NOVEL BUMI MANUSIA - Wiratama, I Wayan Agus; Yoga, Ngurah Artha; Wiastra, I Gede Gita (Wacana : Majalah Ilmiah Tentang Bahasa, Sastra Dan Pembelajarannya, 2023)
This research aims to describe the relationship between the views of Tirto Adhi Soerjo and the character Minke in the novel Bumi Human in terms of feminism. This research was carried out using a qualitative descriptive approach. The data sources are the novel Earth of Mankind by Pramoedya Ananta Toer and the book entitled Tirto Adhi Soerjo Bapak Pers Indonesia (2012) written by M Rodhi As'ad. Data collection instruments are tables in the form of data cards and data analysis tables. Data were analyzed descriptively qualitatively with inductive conclusions drawn. The theory used to solve research problems is intertextuality. The results of data analysis show that Minke's views on feminism are known through the figures Nyai Ontosoroh and Annelies Mellema, there are three struggles for women shown: women's equality in the economic, social and political fields. Tirto Adhi Soerjo views feminism as an important thing. There are two things that Tirto is fighting for for women, namely, women's right to speak through the press and fighting for women to manage the media independently.